Editorial - Kassim, Mohammed (University of Dar es Salaam Library Journal, 2022)
It is great pleasure that we welcome you to Volume no 16, issue no. 2 of the University of Dar es Salaam Library Journal. The articles in this issue mirror the interdisciplinary nature of Library and Information Science. The contributions from authors focus on different themes including Information and Knowledge Management (Moses Mutage & Peterson Dewah; Herbet Hambati; Sumaya M. Kagoya, Gerald Z. P. Tinali, & Jamie Caine; Emmanuel Mkhai & Nakivona H. Rashid); Digital media (Fortunata F. Kirita & Kelefa Mwantimwa; Victor Eliah; Juma J. Masele); Health (Severine S. A. Kessy & Rutasimbila Raymond; Valeria Kyumana; Josephine Rupia & Evans Wema); Research Management and Research Communication (Obadia S. Buhomoli & Paul S. Muneja; Wegene Demeke & Bruce Ryan); and Records Management (Mwombeki Rutta & Esther Ndenje-Sichalwe).